DELPHI-AHP METHOD APPLICATION IN ANALYSIS AND CRITERIA DETERMINATION OF WARSHIP TYPE - Ikhwan Syahtaria; Tunang Arimbo; Ahmadi Ahmadi (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2020)
ABSTRACT Fleet Comando III is the Main Command of the Indonesian Navy as Operation City which is tasked with carrying out defense and security operations of the maritime dimension by carrying out security in the territorial waters of eastern Indonesia. The operation in these waters is faced with the vulnerability of frequent violations, geological conditions consisting of thousands of islands and shallow straits, extreme weather and also with limited state defense budget conditions. Therefore, it is very necessary that warship is appropriate and ready to face these challenges and obstacles so that the goals of the organization can be achieved. The purpose of this study was to analyze the criteria and determine the type of warship needed in accordance with the conditions in Fleet Comando III. This study uses an integration between the Delphi method and the AHP method. The Delphi method is used to determine criteria while the AHP method is used to evaluate qualitative data and determine the weight of each criterion / sub-criteria. Based on this research, it is concluded that from the available alternatives, the best type of warship is combatant warship with a value of 0.299 then fast warship with a value of 0.184, amphibious warship with a value of 0.154, auxiliary warship with a value of 0.131, mine warship with a value of 0.199 and finally submarines with a value of 0.144. The results of this study are expected to be input and consideration for the leadership of the Indonesian. Keywords: Fleet Comando III, Delphi, AHP.